Cord Blood Transplantation in 2 Infants Presenting Monosomy 7 Clonal Hematopoiesis: SAMD9/SAMD9L Germline Mutation. Issue 2 (21st March 2023) - Hirai, Maiko; Yagasaki, Hiroshi; Kanezawa, Koji; Ueno, Masaru; Shimozawa, Katsuyoshi; Imai, Kohsuke; Morio, Tomohiro; Kato, Motohiro; Gocho, Yoshihiro; Narumi, Satoshi; Ebihara, Yasuhiro; Morioka, Ichiro
Abstract : Recently, germline mutations in SAMD9 and SAMD9L were increasingly found in children with monosomy 7. We report the outcomes in 2 infants with the SAMD9/SAMD9L variant, who presented with anemia and thrombocytopenia (patient 1), and neutropenia and nonsymptomatic white-matter-encephalopathy (patient 2). Both patients received cord blood transplantation and experienced critical post–cord blood transplantation adverse events; patients 1 and 2 developed fulminant engraftment syndrome and life-threatening graft-versus-host disease, respectively. Of note, selective loss of chromosome 7 in bone marrow–derived CD34 + cells was inferred.